VO#033 Proposal of extra works for water treatment plant system rev.01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the revised submission of final proposal of cost amount against extra works for water treatment plant system that includes plant supply, transportation, installation etc. for BRACU new campus project.